Perception of Students Towards Bully Awareness Through Drama in Education - Azzahrah, Anuar; Nor Mazlina, Ghazali; Nur Qasdina Jeeta, Abdullah; Syarafina, Abdullah (2021)
Drama in education has been found to be one of the means to counteract bullying issue. It provides a unique educational experience involving both feelings and emotions in a way that results in a more effective form of education. Research has also reported the effectiveness of educational drama in improving student's interpersonal relations, and reducing aggression. This is an action research study involving respondents from Counseling and Theater program. The objectives of the research are to identify perception of students toward bullying issue and their perception on the existing drama that addresses bullying issues. Findings have shown that most students have been involved as a bystander (witness of bully situation). Students also have expressed various feedbacks on the bully drama in terms of their narrative attribution, self-conscious emotions, and coping strategies. The significances of the research are to increase student’s awareness on issues related to bullying and to integrate drama as part of counseling intervention against bullying.